The digital geographies of tact - Mike Duggan (Digital Geography and Society)
This article outlines a research agenda for the spatialities of tact produced by, through and of digital spaces. As a discipline interested in what and who characterises digital space, and in how different relations come to produce space, the article puts forward a proposition for geographers to take tact seriously as an inherently spatial concept useful for theorising the production of space in our digital society. The paper identifies three strands of tact from the literature, 1) tact and social behaviour, 2) tact and touch, 3) tact and judgement, and outlines what they can offer geography in terms of a novel framework for studying digital society. It raises questions of how and why digital spaces and practices produce new trajectories for displays of tact in everyday life, how digital spaces modulate our understanding and experiences of touch, as well as asking whether algorithmic decision making technologies such as Artificial Intelligence have a capacity for tact, and what that means for the geographies these systems shape. The work makes a contribution to the discipline's long standing interests in spatial tactics and socio-spatial behaviour, in touch and sensory geographies, and more recently to algorithmic decision making.